An Unpublished Letter from the Spanish Noble Pedro de Tapia to His Painter Friend Hector Crucer (BSAA arte, 2019)
In the paper a long and unpublished letter, traced in the State Archive of Naples, is published. The letter was sent, in March 1600, from don Pedro de Tapia y Ribera to Naples to the Flemish painter Hector Crucer from Antwerp. In the letter precise iconographic and technical indications were given to the painter to execute three canvases with a Franciscan subject. In the text it’s hypothesised that the triptych was intended for the church of the convent of the Discalced Franciscans of Loja (Granada), founded by don Pedro de Tapia and his wife, doña Clara del Rosal Alarcón, a native of the Andalusian city. Of the Franciscan complex, suppressed in 1835 and demolished in 1951, only the praying statues of the two founders survive. As it’s supposed here, they originally looked at the Crucer’s triptych from two niches in the presbytery of the church. The statues, now housed in the Museo de la Alcazaba of Loja, are here given back to the Genoese marble sculpture of the early seventeenth century dominated by Taddeo Carlone’s workshop.
Keywords: Hector Crucer; Pedro de Tapia; Taddeo Carlone; Nicolas van Aelst; Loja (Granada); Genoese sculpture; triptych; Flemish-Neapolitan painting